Antidiabetic activity of standardized extract of Quassia amara in nicotinamide-streptozotocin-induced diabetic rats - Husain G.M.; Singh P.N.; Singh R.K.; Kumar V. (My University, 2025)
The aim of the present study was to evaluate the efficacy of a standardized methanol extract of Quassia amara L. (Family: Simaroubaceae) in nicotinamide-streptozotocin-induced diabetic rats. Non insulin dependent diabetes mellitus was induced by streptozotocin in rats pre-treated with nicotinamide. Diabetic rats were treated with oral doses of Quassia amara extract (QaE; 100 and 200 mg/kg) or glibenclamide (10 mg/kg; as standard). QaE and glibenclamide were administered as a suspension in 0.3% carboxy methyl cellulose for 14 days. Control animals received an equal volume of vehicle. Blood samples were collected by retro-orbital puncture on day 14, 1 h after last treatment. Plasma glucose, insulin and lipid parameters (total cholesterol, LDL-C, HDL-C and triglycerides) were measured using commercially available biochemical kits. The oral glucose tolerance test was performed to evaluate the effect of the extract on peripheral glucose utilization in normal rats. Both doses of QaE significantly (p < 0.01) reduced elevated fasting blood glucose levels in diabetic rats. In the oral glucose tolerance test, QaE treatment significantly increased (p < 0.05) the glucose tolerance compared with the vehicle. QaE and glibenclamide, effectively normalized dyslipidemia associated with streptozotocin-induced diabetes. The findings of the present study indicate that Quassia amara extract may be potentially valuable in the treatment of diabetes and associated dyslipidemia. Copyright © 2011 John Wiley & Sons, Ltd.